2013
DOI: 10.1002/anie.201304830
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Brønsted Acid Mediated Glycosylation with Recognition of Alcohol Chirality

Abstract: Many carbohydrate-containing natural products, which possess mono-and oligosaccharides, such as proteoglycans, glycoproteins, glycolipids, and antibiotics, are found in nature as important biological substances. A large number of recent biological studies on these glycomolecules at the molecular level have shed light on the biological significance of their carbohydrate units (glycons) in molecular recognition for the transmission of biological information. [1] It is now recognized that carbohydrates are at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…Thus, when ent ‐ 29 was used, the β‐selectivity of the glycosylation dropped significantly under the same reaction conditions. This observation is in line with results from the Bennett and Toshima labs, who reported that stereochemical match and mismatch played a role in chiral phosphoric acid‐catalyzed glycosylations. Later, the Nagorny group applied the chiral phosphoric acid in the regioselective synthesis of aminoglycosides …”
Section: Organocatalysissupporting
confidence: 91%
“…Thus, when ent ‐ 29 was used, the β‐selectivity of the glycosylation dropped significantly under the same reaction conditions. This observation is in line with results from the Bennett and Toshima labs, who reported that stereochemical match and mismatch played a role in chiral phosphoric acid‐catalyzed glycosylations. Later, the Nagorny group applied the chiral phosphoric acid in the regioselective synthesis of aminoglycosides …”
Section: Organocatalysissupporting
confidence: 91%
“…Very recently, Toshima and co-workers reported a novel approach that makes use of the chiral recognition of aglycones. 89 Thus, in glycosylations of racemic alcohols in the presence of a chiral Brønsted acid activator, one enantiomer was glycosylated preferentially and the glycosides were obtained with high stereoselectivity and yields.…”
Section: Effect Of the Glycosyl Acceptormentioning
confidence: 99%
“…A twelve-membered cyclic transition state is invoked in which the phosphoric acid hydrogen simultaneously bonds to the donor and acceptor and preorganizes the latter for an S N 2-type displacement. 89 …”
Section: Counterion and Additive Effectsmentioning
confidence: 99%